2018
DOI: 10.5964/jspp.v6i2.971
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Bringing in the Bystander™ program among first-year students at a religiously-affiliated liberal arts college

Abstract: To address sexual assault, many universities are implementing Bringing in the Bystander™ (BitB) training, a prevention program that aims to improve participants’ bystander self-efficacy and reduce rape myth acceptance. Although growing evidence supports the efficacy of BitB, data primarily have been amassed at one large public university, the University of New Hampshire, limiting the generalizability of intervention effectiveness. To address this gap, we made modifications to training structure and assessed Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Existing research examining non campaign-based prevention programming has also found evidence of differential program impacts based on various individual characteristics (e.g., gender [Inman et al, 2018; Moynihan & Banyard, 2008]; year of study [Kettrey & Marx, 2019]). As these types of variables were examined in a limited capacity within the included sample of studies, future evaluative research of sexual violence prevention campaigns should consider examining individual characteristics more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research examining non campaign-based prevention programming has also found evidence of differential program impacts based on various individual characteristics (e.g., gender [Inman et al, 2018; Moynihan & Banyard, 2008]; year of study [Kettrey & Marx, 2019]). As these types of variables were examined in a limited capacity within the included sample of studies, future evaluative research of sexual violence prevention campaigns should consider examining individual characteristics more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Bringing in the Bystander (Banyard et al., ; Banyard, Moynihan, & Crossman, ; Inman, Chaudoir, Galvinhill, & Sheehy, ; Moynihan & Banyard, ; Moynihan, Banyard, Arnold, Eckstein, & Stapleton, ) is a multicomponent violence reduction curriculum that combines two psychological models: the transtheoretical model of change (Prochaska, DiClemente, & Norcross, ) and the community readiness model (Edwards, Jumper‐Thurman, Plested, Oettin, & Swanso, ). The program utilizes the idea of achieving greater helping behavior through a greater sense of community (Banyard, ).…”
Section: Bystander Informed Violence Reduction Programsmentioning
confidence: 99%
“…The Bringing in the Bystander program has also been subject to several evaluations (Banyard et al., ; Inman et al., ; Moynihan et al., , ; Senn & Forrest, ). These evaluations tend to find decreases in rape myth acceptance and increases in self‐reported feelings of efficacy, willingness to intervene, and acts of intervention.…”
Section: Effectiveness Of Existing Violence Reduction Programsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Exceptions include Inman et al (2018) and Worthen and Wallace (2021). Inman et al recruited a sample of study participants via e-mail and suffered high attrition in the posttest phase, thus introducing potential biases.…”
mentioning
confidence: 99%